Automated generation of semantic descriptions for data services - Wang, Mengran. (2013)
Web service is a popular technology standard to provide machine-to-machine application services. There are many researches on the automated composition of web service to enable orchestration of multiple web services. As a solution to automated web service composition, the Institute for Infocomm Research (I2R) has proposed a technology based on the OWL-S of the Semantic Web technology stack. Semantic Web is a set of technologies aimed to transform the current internet to a web of structured and machine-readable contents services. And OWL-S is a language used to describe web services semantically. In order for I2R’s technology to be accepted, semantic description of web services are the prerequisites. As an effort to accelerate user adoption, a software tool “OWL-S Creator” is developed in this project, which enables the users to automatically generate semantic description for data web services. The OWL-S Creator bridges the gap for the automated creation of semantic service description with its streamlined Graphical User Interface, lightweight-ness and OWL-S-specificity.